PENYELESAIAN KONFLIK ETNIS DAN INSTITUSIONALISASI PENGADILAN LOKAL YANG BERBASIS BUDAYA - Hermansyah Hermansyah (Jurnal Media Hukum, 2012)
Conflict, ethnicity and multicultural matters are natural law, and the conflicts frequently happen are caused by the misunderstanding of the different life objectives, tribe diversity and cultural plurality. In reality, the conflict settlements are often solved through criminal justice system. However, the settlement through the state criminal justice system results in dissatisfaction as it emphasizes more on the procedural justice. People use violence as an expression of their dissatisfaction with the state justice system. In fact there is an institutionalized local justice (customary justice) which can be used to settle conflicts considering that local justice characteristics emphasize more on substantive justice aspects in settling the conflicts and have social basis and base itself on clear cultural based community.